Water-induced rapid hardening of shape memory foam - Lim, Amos Xuan Qi (Nanyang Technological University, 2022)
In recent years, research into the applications of Shape Memory Materials (SMMs) in biomedical settings have been growing in popularity. Shape Memory Materials belong to a group of materials that possess a unique phenomenon called the Shape Memory Effect (SME). Shape Memory Materials can be deformed indefinitely and ‘memorise’ this temporary shape. It can then return to its original form after the right stimulus is applied.